(untitled) (LACCEI, 2024)
Smart Grids represent one of the most important sustainable electrical power systems. Microgrids are vital components of the smart grid, supplying energy to different types of customers in both stand alone or grid connected modes. Therefore, the study of microgrids is of extreme relevance. Massive Open Online Courses (MOOCs) have become a useful alternative for millions of students and professionals that wish to learn about a specific topic. In this scenario the design of a MOOC to study aspects of a microgrid such as Cybersecurity, State Estimation and Optimization represents a step towards the modernization of the education associated with electrical systems. This paper describes the main aspects in the design process of a MOOC in Cybersecurity, State Estimation and Optimization for Electrical Microgrids. The process of design has been supported by the eFellows program administered by the American Society for Engineering Education (ASEE) and funded by the US National Science Foundation (NSF) and the Latin American and Caribbean Consortium of Engineering Institutions (LACCEI). The MOOC includes practical online laboratories using engineering software, such as MATLAB, Python and Google Colaboratory, utilizing real datasets for solar radiation, electrical demand, voltage, current, among other variables. The real datasets, provided by the Ministry of Mines and Energy of the Dominican Republic, have been placed in Open Science Framework’s repository, granting free access to other researchers, professors and students.